Acroterius gen. nov. (Araneae: Linyphiidae: Linyphiinae) with twelve new species from Yunnan, China - Irfan, Muhammad; Bashir, Shahida; Peng, Xianjin (European Journal of Taxonomy, 2021)
Acroterius gen. nov. is described from Yuannan, together with twelve new species: A. absentus gen. et sp. nov. (♂); A. brevis gen. et sp. nov. (♂/♀); A. camur gen. et sp. nov. (♂/♀); A. circinatus gen. et sp. nov. (♂/♀); A. hamatus gen. et sp. nov. (♀); A. inversus gen. et sp. nov. (♀); A. latus gen. et sp. nov. (♂/♀); A. longidentatus gen. et sp. nov. (♀); A. longimultus gen. et sp. nov. (♂/♀); A. longiprojectus gen. et sp. nov. (♀); A. ovatus gen. et sp. nov. (♀), and A. parvus gen. et sp. nov. (♀). Detailed descriptions of genitalic characters and somatic features by means of photographs and line drawings, as well as comparisons with closely related species, are provided.